Prioritas Pelayanan Publik Pemerintah Kota di Indonesia - H.P, Heru Purboyo; Arief, Eldowan; Dirgahayani, Puspita (Journal of Regional and City Planning, 2004)
This article presents one step of chain in formulation of Index of Public Service conducted by the city's government. The Index is used to compare the local government performance in delivering public service of their community. It consist of quantitative indicators which can show the public service given by local government. This article focuses on effort to obtain the weight of each indicator conducted by experts who are assumed they have the authority on urban service. Method of Analytical Hierarchy Process is applied to structure the expert's judgment and then the result is further processed by the Expert Choice software.